The Addition of C, Zn-C, and Sn-C on Anatase Titanium Dioxide (TiO2) for Dye-Sensitized Solar Cells Application - Novianti, Ressa Muhripah; Nursam, Natalita Maulani; Shobih, Shobih; Hidayat, Jojo; Soepriyanto, Syoni (National Research and Innovation Agency (BRIN), 2023)
DSSC (dye-sensitized solar cell) is a third-generation photovoltaic technology that can convert solar energy into electric current using a photoelectrochemical mechanism. Photoelectrode is one of the significant elements in DSSC, where photoexcited electrons are generated, and serves as an electron transport medium. Anatase titanium dioxide (TiO2) is often used as photoelectrode material because of its excellent photoactivity, high stability, non-toxicity, environmental friendliness, and low price. Many DSSC modifications have been conducted to overcome the efficiency limitations in DSSC, and one of them is carried out by modifying the TiO2 via doping. In this study, TiO2 doped with C and co-doping with Zn (Zn-C) and Sn (Sn-C) were prepared using sol-gel reactions, and they were subsequently applied and tested as photoelectrode in DSSC. The results showed that undoped and doped TiO2 had a porous spherical morphology with inhomogeneous particle sizes. The addition of C, Zn-C and Sn-C dopants has reduced in the crystallite size and the band gap energy of TiO2. The efficiency of DSSC with undoped TiO2 DSSC was 3.83%, while the best performance was obtained from DSSC C-TiO2 with an efficiency of 4.20%. In contrast, the DSSC with Zn-C-TiO2 and Sn-C-TiO2 co-doping produced unexpectedly lower efficiency of 0.71% and 0.85%, respectively.